Effect of different wing geometries on their vibration characteristics - Hmoad, Nassear R.; Ali, Anmar H.; Saadoon, Ali Malik; Abdulkareem, Aveen A.; Albayati, Amjed H. (Frontiers in Mechanical Engineering, 2026)
Understanding how wing geometry and internal structural configuration influence vibration behavior is essential for ensuring the aeroelastic stability and structural integrity of modern aircraft. This study presents a comprehensive numerical investigation of the modal and deflection characteristics of aircraft wings with different geometries (symmetric tapered planform and swept-back) and spar configurations (box and I-section) using the finite element method (FEM) in ANSYS Mechanical APDL R.15. Six NACA airfoil profiles (0024, 2411, 2416, 2424, 4412, and 4421) with angle of attack 9° under 50 m/s speed and 1,100 kg pay load were analyzed under identical aerodynamic and material conditions using linear elastic and small-deformation theory. Aerodynamic coefficients were determined using thin airfoil and Prandtl’s lifting-line theories, while modal parameters were extracted through high-order 20-node solid brick elements and verified through mesh convergence analysis. Based on the results obtained, the tapered wings show a natural frequency nearly 22% higher than swept-back wings. The matter that confirms the dominant influence on geometric stiffness. On the other hand box spar wings reveal 9.5%–22% higher frequencies but showed 20%–30% higher deflection than I-section spars, demonstrating their superior torsional compliance and enhanced energy absorption under the dynamic effect. On the contrary, I-section spar resulted in higher bending stiffness and lower deformation, especially in higher-order modes. Based on airfoil series, the more the thick NACA 0024 as well as 2424 profiles revealed the highest levels of stiffness, based on 6th mode frequency that exceeded 250 Hz, but the thinner cambered sections like NACA 4412 and 4421 exhibited compliance and limited rigidity against torsion. Based on the findings, the obtained increase in the natural frequency and the reduced deflection with stiffer geometries reflect improved resistance to aeroelastic instability like flutter onset. A statistical analysis using ANOVA verified that the geometry of the wing has a statistically more significant effect on modal response than the spar type although both have a significant influence on vibration behavior. Furthermore, the result of analysis concludes that the taper wings reinforced with spars type I-section give the most balanced combination of weight efficiency, stiffness and stability against vibration for the aircraft type medium payload.